Non-Governmental Organization and The Politics of Environmental Sustainability at Meratus Mountain Karst in South Kalimantan, Indonesia - Siti Hamidah; Muhammad Nizar Hidayat (International Journal of Southeast Asian Studies (IJSAS), 2021)
The planned opening of the Meratus Mountain Karst coal mine located in Hulu Sungai Selatan Regency, South Kalimantan Province, Indonesia sparked local NGOs, namely WALHI (Wahana Lingkungan Hidup Indonesia) South of Kalimantan, to oppose the commercialization and exploitation of karst areas. Nevertheless, it is undoubtedly exciting to see the characteristic discourse, mission, methods, capabilities, and patterns of NGO alliances and the specific issues they are fighting. The study aims to look at how WALHI South Kalimantan makes efforts and ways to protect the mountainous karst region of Meratus and what factors influence them to adopt the way. This research approach is qualitative research and is a combination of desk research and field research. Several strategies can be identified as WALHI's instruments in fighting for their interests in the politics of managing the Meratus Karst area, namely: 1) Demonstrations, 2) Seminar/ FGD, and 3) Campaign, and 4) Legal efforts. WALHI, in their actions, did not go alone, especially in the demonstrations they carried out. They carried out their actions on behalf of the South Kalimantan Karst Care Community Alliance (AMPK). WALHI created a flexible and open organizational structure to collaborate with other NGOs who share their goals.